2022
DOI: 10.1002/advs.202105569
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Coherent Propagation of Organic Exciton‐Polaritons through Dark State Delocalization

Abstract: While there have been numerous reports of long-range polariton transport at room-temperature in organic cavities, the spatiotemporal evolution of the propagation is scarcely reported, particularly in the initial coherent sub-ps regime, where photon and exciton wavefunctions are inextricably mixed. Hence the detailed process of coherent organic exciton-polariton transport and, in particular, the role of dark states has remained poorly understood. Here, femtosecond transient absorption microscopy is used to dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
79
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 75 publications
(174 reference statements)
6
79
2
Order By: Relevance
“…Moreover, a rough estimate of the expansion velocity gives a value of ∼ 176 µm/ps, roughly two thirds the speed of light. This value is more than two orders of magnitude larger than observed for polaritons in any previous time-resolved measurements conducted in Fabry-Pérot cavity systems 7,13,19 . In fact, this estimated velocity approaches the polariton group velocity at the same location on the lower BSWP branch (point B in Fig.…”
Section: Dynamics Measurements and Resultscontrasting
confidence: 52%
See 4 more Smart Citations
“…Moreover, a rough estimate of the expansion velocity gives a value of ∼ 176 µm/ps, roughly two thirds the speed of light. This value is more than two orders of magnitude larger than observed for polaritons in any previous time-resolved measurements conducted in Fabry-Pérot cavity systems 7,13,19 . In fact, this estimated velocity approaches the polariton group velocity at the same location on the lower BSWP branch (point B in Fig.…”
Section: Dynamics Measurements and Resultscontrasting
confidence: 52%
“…In particular, we have observed how polaritons, excited in a metallic, planar cavity, gradually migrate and reach distances which are ∼ 5 µm away from their initial position, within several picoseconds. Interestingly, these studies found that the polariton velocity was much lower than expected by simple considerations 7,13 . While the dispersion of cavity polaritons predicts a group velocity on the order of 20 µm/ps, the observed velocities were smaller than 1 µm/ps, pointing toward a fundamental gap in the understanding of cavity polaritons.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations